Aerobic and anaerobic contribution to Wingate test performance in sprint and middle-distance runners - Granier, P.; Mercier, B.; Mercier, J.; Anselme, F.; Prefaut, C. (European Journal of Applied Physiology, 1995)
We investigated the aerobic and anaerobic contributions to performance during the Wingate test in sprint and middle-distance runners and whether they were related to the peak aerobic and anaerobic performances determined by two commonly used tests: the force-velocity test and an incremental aerobic exercise test. A group of 14 male competitive runners participated: 7 sprinters, aged 20.7 (SEM 1.3) years, competing in 50, 100 and 200-m events and 7 middle-distance runners, aged 20.0 (SEM 1.0) years, competing in 800, 1,000 and 1,500 m-events. The oxygen uptake (VO2) was recorded breath-by-breath during the test (30 s) and during the first 20 s of recovery. Blood samples for venous plasma lactate concentrations were drawn at rest before the start of the test and during the 20-min recovery period. During the Wingate test mean power (W) was determined and three values of mechanical efficiency, one individual and two arbitrary, 16% and 25%, were used to calculate the contributions of work by aerobic (Waer,ind,16%,25%) and anaerobic (Wan,ind,16%,25%) processes. Peak anaerobic power (Wan,peak) was estimated by the force-velocity test and maximal aerobic energy expenditure (Waer,peak) was determined during an incremental aerobic exercise test. During the Wingate test, the middle-distance runners had a significantly greater VO2 than the sprinters (P < 0.001), who had significantly greater venous plasma lactate concentrations (P < 0.001).